2020
DOI: 10.1108/ijphm-12-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

How does perceived cost and value influence pharmacy patronage? A scoping review

Abstract: Purpose To date, community pharmacy research has largely focused on the impact of service quality elements on patronage behavior. Investigation into the influence of cost and value is limited. The purpose of this study is to explore what is known about customers’ perceptions of cost and value, and how these influence patronage patterns in community pharmacy. Design/methodology/approach A scoping review framework was used to conduct a systematic search of four databases with the addition of articles sourced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…In our scale, we used items that reflect this narrative, but one that is more extreme where psychological conditions are the primary means by which one protects oneself against COVID-19. In health product use, individuals tend to take into account trade-offs in time, price, and psychological costs (Grew et al, 2020). Therefore, our findings might be explained in that due to being relatively low-cost means of protection, at least compared to buying and using commodities, one might prefer the lower cost option.…”
Section: Discussionmentioning
confidence: 99%
“…In our scale, we used items that reflect this narrative, but one that is more extreme where psychological conditions are the primary means by which one protects oneself against COVID-19. In health product use, individuals tend to take into account trade-offs in time, price, and psychological costs (Grew et al, 2020). Therefore, our findings might be explained in that due to being relatively low-cost means of protection, at least compared to buying and using commodities, one might prefer the lower cost option.…”
Section: Discussionmentioning
confidence: 99%
“…In the comments classified as assortment [ 36 ], it is observed that customers seek not only access to the manufacturers’ products but also the availability of a variety of products, as exemplified below:…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…, 2016). However, there seems to be minimal studies that look into the impact of costs and how it may affect their patronage patterns (Grew et al. , 2020) including green purchase.…”
Section: Introductionmentioning
confidence: 99%